Development of adsorbent from Mentha plant ash and its application in fluoride adsorption from aqueous solution: a mechanism, isotherm, thermodynamic, and kinetics studies - Bhan C.; Singh J.; Sharma Y.C. (My University, 2025)
In the present study, Mentha plant ash was modified by Na and Al for the synthesis of adsorbent and applied for the removal of Fluoride from an aqueous solution. Mixture of acid washed Mentha plant ash (MPA) and NaOH (in the ratio 1:1.3) thermally treated at 600°C in a muffle furnace then treated with aqueous solution of sodium aluminate. The characterization of sodium aluminum modified ash (Na-Al-MA) powder was done such as SEM (Scanning Electron Microscopy), Particle Size Analysis (PSA), Fourier transformed spectroscopy (FTIR), Zeta Potential, XRD (X-ray Diffraction) analysis, and Brunauer–Emmett–Teller (BET) analysis. The removal of fluoride from an aqueous solution carried out with Na-Al-MA by batch adsorption process. The Na-Al-MA was found to be very effective as adsorbent. The maximum removal of fluoride was achieved ̴ 86% at neutral pH and at room temperature. It was investigated that Langmuir adsorption isotherm and pseudo-second-order kinetic was best fitted for fluoride adsorption. The fluoride adsorption on Na-Al-MA was an exothermic process. A possible mechanism including electrostatic attraction, hydrogen bonding, and metal-fluoride interaction for fluoride adsorption on Na-Al-MA have described in this study. Novelty statement: Utilization of Mentha plant ash for the development of adsorbent and its application in adsorptive removal of fluoride from aqueous solution is the novelty of this work. Adsorbent preparation may be the better way of waste biomass management. © 2021 Taylor & Francis Group, LLC.